Malay-European Interfaith Discourse in Historical Perspective - Mohd Zarif, Muhammad Mustaqim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
As a multiracial country, Malaysia faces pressing trans-religious issues that could lead to tensions and conflicts if not properly managed. While acknowledging the importance of interfaith discourse and interreligious relations, current initiatives taken are yet to achieve its intended aims due to resistance from certain segments of the Muslims that viewed those initiatives as a direct threat to the supremacy of Islam in the country. At the same time, it is found that not much consideration is given to the social and historical experiences of the local populace in this matter, especially in the periods prior to the 20th century. Therefore, this paper aims to explore the nature of historical and social encounters between the Malay-Muslims and European Christians in terms of their perception and attitude towards other religions; identify cases of interfaith discourse and analyse its socio-political settings; and asses the role of the rulers and ulama in influencing the direction of interfaith discourse among the Malays. It is hoped that this historical reconstruction will help enrich our understanding of the nature, issues, and challenges faced today and charting the future direction of the interfaith dialogue in the country.